2009
DOI: 10.1017/s0952523809990149
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological characterization, localization, and regulation of ionotropic glutamate receptors in skate horizontal cells

Abstract: Glutamate is believed to be the primary excitatory neurotransmitter in the vertebrate retina, and its fast postsynaptic effects are elicited by activating NMDA-, kainate-, or AMPA-type glutamate receptors. We have characterized the ionotropic glutamate receptors present on retinal horizontal cells of the skate, which possess a unique all-rod retina simplifying synaptic circuitry within the outer plexiform layer (OPL). Isolated external horizontal cells were examined using whole-cell voltage-clamp techniques. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 61 publications
(160 reference statements)
0
8
1
Order By: Relevance
“…They concluded that the extracellular calcium concentration influences the effects of a high inhibitory (1 mM) but not a low potentiating (10 μM) concentration of zinc. These findings contrast with findings in skate retinal horizontal cells (Kreitzer et al, 2009). Kreitzer et al (2009) reported that inhibition of AMPAR-mediated responses to application of 100 μM glutamate by high concentrations of zinc (300 μM and 1 mM) was enhanced at lower extracellular concentrations of Ca2+ (0.2 mM Ringer's solution) (Kreitzer et al, 2009).…”
Section: Mechanism(s) Of Zinc-mediated Inhibitioncontrasting
confidence: 60%
“…They concluded that the extracellular calcium concentration influences the effects of a high inhibitory (1 mM) but not a low potentiating (10 μM) concentration of zinc. These findings contrast with findings in skate retinal horizontal cells (Kreitzer et al, 2009). Kreitzer et al (2009) reported that inhibition of AMPAR-mediated responses to application of 100 μM glutamate by high concentrations of zinc (300 μM and 1 mM) was enhanced at lower extracellular concentrations of Ca2+ (0.2 mM Ringer's solution) (Kreitzer et al, 2009).…”
Section: Mechanism(s) Of Zinc-mediated Inhibitioncontrasting
confidence: 60%
“…Similarly, AMPA and kainate receptor subunits were detected in the teleost retina (Peng et al, 1995;Vandenbranden et al, 2000;Klooster et al, 2001). These anatomical data apparently are in conflict with most electrophysiological studies, which report that only AMPA receptors contribute to the postsynaptic glutamate response (Yang et al, 1998;Blanco & de La Villa, 1999;Kreitzer et al, 2009). However, the functional presence of both AMPA and kainate receptors has been shown in human retinal horizontal cells (Shen et al, 2004).…”
Section: Expression Of Ampa Receptors On Horizontal Cell Dendritesmentioning
confidence: 98%
“…As horizontal cell bodies do not generate Na + -dependent action potentials, changes in release kinetics modulate their membrane potential in a graded fashion. Most electrophysiological studies have found evidence for expression of AMPA receptors only (Yang et al, 1998;Blanco & de La Villa, 1999;Kreitzer et al, 2009), but immunocytochemical and ultrastructural data indicate the presence of both AMPA and kainate receptors at invaginating horizontal cell dendrites (Brandst€ atter et al, 1997;Hack et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Functional CP-GluARs have been found in horizontal cells of every species investigated, including lizard (Jackman et al, 2011), fish (Eliasof and Jahr, 1997; Huang and Liang, 2005; Sun et al, 2010), skate (Kreitzer et al, 2009), and rabbit (Rivera et al, 2001; Figure 1B). Catfish cone horizontal cells, stellate neurons with enormous somata (Sakai and Naka, 1986), express extraordinarily fast CP-GluARs: in excised membrane patches at room temperature, glutamate-evoked currents desensitized with a time constant of ∼1 ms and recovered from desensitization with a time constant of less than 9 ms (Eliasof and Jahr, 1997).…”
Section: Cp-gluars In Horizontal Cells Mediate Positive Feedback Ontomentioning
confidence: 99%